Formative evaluation for Mandarin courseware enhancement / Norlina Mohd Sabri, Hasiah Mohamed @ Omar and Goh Ying Soon - Mohd Sabri, Norlina; Mohamed @ Omar, Hasiah; Ying Soon, Goh (2012)
Learning Mandarin as the third language has always been difficult to the Bumiputera students at Universiti Teknologi MARA (UiTM) Terengganu. Due to the time constraint in class, most of the students are having problem to memorize the correct Mandarin pronunciations after each lesson. To overcome this problem, a Mandarin courseware has been developed with the aim to help especially the beginner students to improve in Mandarin pronunciations and speaking skills. The courseware, which combines all the multimedia elements, could be a very effective tool for the teaching of Mandarin as a foreign language to the students. In order to guarantee the quality of the courseware as an effective educational tool, a formative evaluation of the Mandarin courseware has to be conducted before it could be formally used as a supplementary learning material. Formative evaluation is the judgments of the strengths and weakness of the interface in its developing stages, for the purpose of revising the navigation. To produce an instructionally-sound courseware package, researchers should always carry out formative evaluation of the product, or even ongoing evaluation at its different stages from prototype to final version. The prototype multimedia courseware has to be checked throughout the stages of design and development so that errors could be detected.